An Intrinsic Oscillation of Gene Networks Inside Hair Follicle Stem Cells: An Additional Layer That Can Modulate Hair Stem Cell Activities - Daszczuk, Patrycja; Mazurek, Paula; Pieczonka, Tomasz D.; Olczak, Alicja; Boryń, Łukasz M.; Kobielak, Krzysztof (Frontiers in Cell and Developmental Biology, 2020)
Here we explore and summarize recent progress made in the characterization of main players in the regulation of hair follicle cyclic regeneration. Particularly, we exchange current views about new discoveries of molecular mechanisms that allow hair follicle stem cells (hfSCs) to synergistically integrate their own homeostasis during quiescence and activation. Moreover, we elaborate on a model showing how different populations of skin stem cells coalesce their intrinsic and extrinsic mechanisms, resulting in the maintenance of their stemness and hair regenerative potential during an organism’s lifespan. Primarily, we focus on the question of how the intrinsic oscillation of gene networks in hfSCs sense and respond to the surrounding niche environment. Furthermore, we investigate the existence of a cell-autonomous mechanism and the reciprocal interactions between molecular signaling axes in hfSCs and niche components. This demonstrates its critical driving force in either the activation of whole mini-organ regeneration or quiescent homeostasis maintenance. These exciting novel discoveries in skin stem cells and surrounding niche components propose a model of the intrinsic stem cell oscillator which is potentially instructive for translational regenerative medicine. Thus, further deciphering the distribution of the molecular signals coupled with their oscillation nature within the stem cells and niche environment may impact the speed and efficiency of testing various approaches to stimulate the development of self-renewal and cell-based therapies for hair follicle stem cell regeneration.